KAJIAN TENTANG EKSISTENSI GENDER DALAM PERSPEKTIF ISLAM - Tanwir, Tanwir (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2017)
This paper discusses the concept of gender in Islam. By using the normative approach through text analysis of Qur'anic and Hadith theology, gender in Islam highly upholds the value of justice regardless of gender. In the Qur'an are found several verses that become supporters and amplifiers that imply a difference, and each has a privilege. However, no verse has been found that describes such distinctions and differences. Thus, Islam has never taught the existence of differences between men and women because it really distinguishes only the level of piety of the Creator.